Essential oil of Thai basil: natural remedy for urolithiasis? - Abd Hamid, Shafida; Darnis, Deny Susanti; Mat Shaari, Nurul Elyni (2013)
Allah (s. w. t.) mentioned in the Qur’an, “And also corn, with (its) leaves and stalk for fodder and sweet scented plants (rayhan)” (Surah Al-Rahman, 55:12). According to Ibn Qayyim, the word ‘rayhan’ referred to every plant with pleasant scent. The Arabs associated this with myrtle, while people of Iraq and Syria gave this name as sweet basil. Basil, scientifically known as Ocimum basilicum is derived from Lamiaceae family. It has been recognized as aromatic plant with the presence of essential oil containing specific volatile components. Traditionally, basil has been extensively utilized in food as a flavoring agent and in perfume and medical industries. Medicinal plants used in traditional antiurolithic therapy have revealed their therapeutic potential. Saponin, lupeol and lupeol linoleate are examples of chemicals constituents found to be able to treat kidney stone. Following previous studies, we decided to examine the chemical components of essential oil of Thai basil (Ocimum bacilicum L) and investigated its effect on induced calcium oxalate or kidney stones.